Literature of the Mamluk Qur'an Art - Aygan, Abdurrahim (Şırnak Univ, 2022)
According to the examples that have survived to the present day, the writing of the mushaf became systematic during the Umayyad period in the 8th century, and it made great progress in terms of writing and ornamentation in Baghdad during the Abbasid period. The Mongol invasion, which deeply affected Islamic culture and civilization in the middle of the 13th century, caused the mushaf writing tradition in Baghdad to be interrupted for a while. The Mamluks, who had stopped their progress by fighting the Mongols at the establishment stage, emerged as a power in the Islamic world in this period. After the capital city of Cairo, they added Syria to their lands and turned these two cities into cultural centers. Since the reign of Sultan Baybars, the power of the slaves did not hold back from the construction activities. In addition to mosques, madrasas and tombs, they built structures unique to Sufis called hankah. A remarkable development is observed not only in the field of architecture but also in book arts. It is seen that the Mamluk sultans had a special interest in the writing of the Qur'an. At the beginning of the 14th century, qualified mushafs were prepared in Cairo and Damascus in terms of both writing and decoration. Especially the Qur'an, which was prepared under the auspices of the sultans, is considered among the rarest examples in terms of Qur'anic art. A group of Qur'an prepared during the reign of Sultan Esref Saban, especially the work that was prepared under the supervision of Sultan Baybars I and exhibited in the British Museum today, is valuable in that it shows the point reached by the mushaf art in the Mamluk period. It is understood from the examples that have survived to the present day that the Mamluk sultans had a special interest in large size Qur'ans in this period. Some of these Qur'an were prepared in a single volume or in juz. In addition to these, volumes of Mamluk mushafs, the number of which we do not know yet, are preserved in different museums and libraries around the world. Although this period is a rich period in terms of quantity and quality, the studies on this field are not sufficient. Many of the Mamluk Qur'ans have not yet been unearthed. Two elements are important in Mamluk Qur'an studies. The first is grouping the works according to their physical qualities. This classification may be according to the size of the mushafs or according to the number of volumes. The other factor is the factors that affect the writing of the Qur'an. Here, we come across a multifaceted field such as the institutional structures of the Mamluks, their socio-cultural identity, the political environment of the period and the personal attitudes of the sultans. This shows that the Qur'an of the Mamluk period can be handled in many different dimensions. In Mamluk Qur'an studies, the first thing to be determined - as in all social sciences - is the discovery and promotion of the literature. This study focuses on the literature that developed within the framework of the Qur'anic art of the Mamluk period. Studies on the subject were identified and discussed in different groups. In this context, four different groups emerged. These are listed as independent studies on Mamluk mushafs, studies on culture and art of the Mamluk period, studies on the art of the Qur'an, and studies on the art of calligraphy and illumination. In the first group, a book, a thesis and three articles; three books, four articles and a thesis in the second group; in the third group, five books and three book chapters, some of which are in them; In the fourth group, a book and a book chapter were identified. These identified studies were introduced, their contents and discussion topics were emphasized and their relations with the art of mushaf were tried to be determined. It is aimed that this literature study will contribute to new studies in the field of Mamluk mushafs.
Keywords: Art of the Qur'an; Mamluk Art; Qur'an Art of the Mamluk; Qur'ans of the Mamluk